Architectural Innovation and Modular Corporate Forms - Galunic, D. Charles; Eisenhardt, Kathleen M. (Academy of Management Journal, 2001)
Based on an intensive and inductive study of a Fortune 100 corporation, this article describes how dynamic capabilities that reconfigure division resources?that is, architectural innovation?may operate within multibusiness firms. We suggest envisaging corporate divisions as combinations of capabilities and product-market areas of responsibility (charters) that may be recombined in various ways, highlighting the interplay of economic and social imperatives that motivate such recombinations. We detail the microsociological patterns by which such recombinations occur and then theorize about an organizational form, termed ?dynamic community,? in which these processes are embedded.